2013
DOI: 10.1080/1612197x.2013.773688
|View full text |Cite
|
Sign up to set email alerts
|

Quiet eye training promotes challenge appraisals and aids performance under elevated anxiety

Abstract: (2012) Quiet eye training promotes challenge appraisals and aids performance under elevated anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 32 publications
3
40
2
2
Order By: Relevance
“…This strategy might involve changing perceptions of resources through the development of confidence, achievement goals, or perceptions of control (Jones, Meijen, McCarthy, & Sheffield, 2009). Research has found that it is possible to facilitate positive cognitive appraisal (states of challenge) and subsequent performance on simple tasks (Moore, Vine, Freeman, & Wilson, 2013).…”
Section: Cognitive (Re)appraisalmentioning
confidence: 99%
“…This strategy might involve changing perceptions of resources through the development of confidence, achievement goals, or perceptions of control (Jones, Meijen, McCarthy, & Sheffield, 2009). Research has found that it is possible to facilitate positive cognitive appraisal (states of challenge) and subsequent performance on simple tasks (Moore, Vine, Freeman, & Wilson, 2013).…”
Section: Cognitive (Re)appraisalmentioning
confidence: 99%
“…It has been theorised that emotional responses in challenge and threat states can be similar, although in the context of challenge, anxiety is seen as a helpful stimulus for performance . There is some support for this proposition, although there are also data showing challenge states to be similar to threat states in terms of anxiety and perceptions of the helpfulness of anxiety, and in some studies challenge states have been associated with both lower levels of anxiety and more facilitative interpretations of anxiety …”
Section: Introductionmentioning
confidence: 99%
“…12 There is some support for this proposition, 15 although there are also data showing challenge states to be similar to threat states in terms of anxiety and perceptions of the helpfulness of anxiety, 16 and in some studies challenge states have been associated with both lower levels of anxiety and more facilitative interpretations of anxiety. 17 Although individual resources are important in determining the nature of the stress response, social aspects also matter. In particular, responses to stress may be influenced by how connected a person feels to his or her team and leader.…”
Section: Introductionmentioning
confidence: 99%
“…In another line of research, the so-called "quiet eye"-a final visual fixation of at least 100 ms directed at a certain location or target (e.g., golf ball, basketball hoop, bull's eye) before movement execution-has been shown to be associated with enhanced performance of tasks with specific targets (Moore, Vine, Freeman, & Wilson, 2013;Vickers, 1996). Whereas various possible accounts of this phenomenon have been offered (for a review, see Vickers, 2009), it seems likely that an external attentional focus promoted by the visual focus on an external object is at least partially responsible for the performance effects (Vine, Moore, Wilson, 2011.…”
Section: Other Lines Of Attentional Focus Researchmentioning
confidence: 99%